The Essential Nawal El Saadawi : a Reader. - Horst, Adele Newson (Zed essential feminists., 2010)
Featuring work never before translated into English, The Essential Nawal El Saadawi gathers together a wide range of Saadawi's writing. From novellas and short stories to essays on politics, culture, religion and sex; from extensive interviews to her work as a dramatist; from poetry to autobiography, this book is essential for anyone wishing to gain a sense of the breadth of Saadawi's work.